Parto domiciliar planejado na ?tica de mulheres e enfermeiras obstetras - Peixoto, Suzana Macedo (2022)
Introduction: Currently, Brazilian obstetric care is based on the technocratic, biomedical and hospital-centered model. In this context, planned home birth, although still little explored, is an option compared to this conventional care and an attempt by women to experience a dignified, respectful and humane birth. It represents, for obstetric nurses, an alternative professional practice in accordance with the humanized model, with autonomy and freedom. Study topic: The experience of planned home birth from the perspective of women and obstetric nurses in Feira de Santana-BA and Salvador-BA. Research question: How is the experience of planned home birth from the perspective of women and obstetric nurses in Feira de Santana-BA and Salvador-BA? Objective: To understand the experience of planned home birth from the perspective of women and obstetric nurses. Method: Qualitative, descriptive study, carried out in Feira de Santana-BA and Salvador-BA. Participants were 07 women who experienced planned home births and 09 obstetric nurses who provided or provide this assistance. Data collection was performed through semi-structured interviews. Data were analyzed using Bardin's content analysis technique. It was approved by the Research Ethics Committee of the State University of Feira de Santana under opinion number 5.041.212. Results: Six analytical categories emerged: The experience of obstetric nurses in assisting Planned Home Birth: motivations, obstacles and challenges; The practices of obstetric nurses in Planned Home Birth assistance; Intercurrences and transfers in Planned Home Birth: the experience of obstetric nurses; Impacts of the pandemic on Planned Home Birth assistance; The experience of women who opt for Planned Home Birth; Companion in Planned Home Birth. Final considerations: The reasons that lead both women and obstetric nurses to opt for planned home birth stem from dissatisfaction with the hegemonic model and the desire for changes in the labor and birth scenario. Obstetric nurses are qualified and trained professionals, who understand the parturition process as a physiological and family event, with women as protagonists. These professionals have a care practice centered on women and based on humanization, scientific evidence and good practices, even during the COVID-19 pandemic, with the challenges and adaptations that came with it. This reflects positively on the health of women and newborns, with fewer interventions, lower risk of complications and morbidity and mortality, as well as the quality of care and satisfaction. Women who choose home as the place to give birth are not uninformed or adherents to a fad. They make a solid choice based on quality information, which makes it possible to make that decision safely and consciously. Contributions: elaboration of a booklet with the theme Planned home childbirth, with the aim of offering quality information so that women can be encouraged and strengthened to think about normal birth and planned home birth, since choosing them implies facing all the system and much of society. It also represents giving visibility to the absence of public policies for this issue in Brazil.